The sword of Tipu Sultan : a historical novel about the life and legend of Tipu Sultan of India - Bhagwan S. Gidwani (New Delhi : Rupa, 2023)
This historical novel tells the story of Tipu Sultan the man, the lover, the soldier, the prince, and the king. It speaks of those who loved and betrayed him; of charming ladies and brilliant men around him; of his greatness and of the crafty stupidity of his contemporaries; os the wit and folly of his times; and of the struggle of men and ideas when faced with the march of history. Based on extensive research and original sources, The Sword of Tipu Sultan is an original contribution to historical literature which gives insights into the character of its hero, and the period in which he lived.
Keywords: Fiction; Karnataka (India) Kings and rulers Fiction; Tipu Sultan